Otimização, seleção e apontamento de arranjos lineares de antenas através da técnica de otimização por enxame de partículas - Souto, Victoria Dala Pegorara (2017)
The Particle Swarm Optimization Technique has been widely studied by researchers, since they act as a stochastic optimization process which can be applied in many areas, for instance in electromagnetism. Researches have evaluated Particle Swarm Optimization in electromagnetic problems, since those usually are very complex and do not present practical analytical solutions. This work employs the Particle Swarm Optimization Technique to perform the optimization of a Linear Antennas Array composed of punctiform sources. This optimization aims to obtain a reduction in the Side Lobes Levels and Half Power Beamwidth of a Linear Array, besides having the main lobe pointed to specific directions. To this end, the antennas of the array must be turned on/off to obtain the desired radiation pattern must be selected. The optimization cases presented in this work use continuous and discrete variables, so in this work a new version of the Optimization by Particle Swarm Optimization technique was proposed, which considers continuous and discrete variables simultaneously.